PEMBANGUNAN PERTANIAN TANAMAN PANGAN BERBASIS KOMODITI UNGGULAN DAERAH KABUPATEN KONAWE - Yohanes Boni (Mega Aktiva, 2025)
The aim of this research is to analyze regional superior commodities and the feasibility of investing in superior food crop farming in the Konawe Regency. Data collection methods include regional surveys, in-depth interviews, and Focus Group Discussions (FGD). Using class typology analysis, location quotient (LQ) analysis, farming margin analysis (MUT), and investment feasibility analysis. Results of typology analysis of regional leading sector rankings in the agricultural sector and mining sector. Analysis of Location Quotien (LQ) and Farming Margin (MUT) of the region's leading commodities, rice fields, superior potential commodities, corn and soybeans. Analysis of investment feasibility through the criteria of NPV, B/C Ratio, PBP, and BEP for lowland rice, corn and soybean farming businesses worthy of becoming superior commodities in the Konawe Regency areas. The results Keywords: Food crop farming, superior commodities, investment feasibility, Location Quotien, Farming Business Margin. the survey and Focus Group Discussion (FGD) show that the superior commodity of lowland rice has production continuity, absorbs a large workforce, farmers have farming skills, and food crop infrastructure is getting better. The problem is that the land for rice farming is optimal, middlemen control the prices of food crop commodities and the younger generation is less interested in working in food crop farming. The findings of this research provide opportunities for further research, with a concentration on increasing the added value of regional superior food crop commodities. Research can be carried out over a longer period of time to observe the dynamics of problems developing superior food crop commodities, the performance of food crop farming businesses, and models of empowering the younger generation in food crop farming activities.